Medication errors in prescription of chemotherapy regimens: A prospective observational study among cancer patients at Iranian referral hospital - Sahar Karimi; Mehrnaz Vaez; Amir Aria; Azadeh Moghaddas (Caspian Journal of Internal Medicine)
Background: Medication errors are a significant cause of adverse events in cancer patients. The study aimed to investigate unintentional medication errors during chemotherapy regimen prescription. Methods: During the six months’ follow-ups, 201 adult patients admitted to outpatients’ chemotherapy ward of Omid Hospital, Isfahan, Iran were examined. An information checklist by the aim of data gathering including patients' demographic information, laboratory data, medications history, chemotherapy drug doses and protocol of administration, pre-medications drugs, and supportive treatment was prepared. The data was compared by standard guidelines and data were presented in percent and frequency. Results: Among the enrolled patients, 327 errors were identified. Sixty-five percent of patients were females and the mean age of patients was 49.2±2.8 years old. Gastrointestinal and breast cancers were among the most frequently reported cancers. The highest frequency of errors (67.27%) was attributed to the prescription of pre-medication drug administration primarily in the management of chemotherapy-induced nausea and vomiting. Medication errors in selection and volume of infused serums (20.18%) and in adjusting the dosage of chemotherapy regimens (10.39%) were the most observed errors. Conclusion: This study highlighted the important areas to improve cancer management at the medical center. By addressing these challenges and implementing necessary changes, the center can enhance the quality of care provided to cancer patients, ensure adherence to international standards, and improve patient outcomes.